ISLAMIC VALUES-BASED LEADERSHIP AS THE KEY TO EDUCATIONAL MANAGEMENT TRANSFORMATION - Alfi Alfaridli, Muhammad; Agus R, Abu Hasan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research examines the role of leadership based on Islamic values in transforming educational management, especially in Islamic educational institutions. Using a qualitative approach with a case study method, this research collected data through in-depth interviews, direct observation, and document study at Mts Ulil Albab. The research results show that applying Islamic values such as justice, trust, and deliberation in leadership significantly contributes to positive changes in educational management, including improving teacher and student performance. These findings also reveal that collaboration based on Islamic principles can create a more productive and ethical learning environment. The implication of this research is the importance of integrating Islamic values in policies and managerial practices in Islamic schools to achieve a more sustainable and meaningful transformation in education.